IMPLIKASI HUKUM PUTUSAN PAILIT TERHADAP JABATAN NOTARIS DAN AKTA YANG DI BUATNYA (Studi Putusan Nomor 20/Pdt.Sus-Pkpu/2020/Pn Niaga Sby) - Narenggar Daranindra Pasca Archqueta (LPPM IAI Almuslim Aceh, 2024)
Article 9 paragraph (1) letter a of Law No. 30 of 2004 combined with Law No. 2 of 2014 regarding the functions of notaries when the notary is temporarily dismissed due to “bankruptcy proceedings or postponement